Asymptomatic Late Migration of an Atrial Pacemaker Lead into the Right Lung. (12th November 2014) - De Schryver, Nicolas; Marchandise, Sebastien; Colin, Geoffrey C.; Ghaye, Benoît; le Polain de Waroux, Jean-Benoît
Abstract : This report illustrates an unusual case of asymptomatic late cardiac perforation by an atrial pacemaker lead into the right lung. In the present case, the lead was explanted by simple manual traction through the device pocket without any complications.